DESAIN VIDEO BASED LEARNING PADA MATA KULIAH AERONAUTICAL INFORMATION SERVICE - Arti, Endang Sugih; Amir , Elfi; Endrawijaya, Ika; Anggraini , Dian; Wagini , Dini; Sadiatmi , Rini; Sinaga , Togi A. Maruli; Muzaki , Mochamad Faisal (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
This study is to design video-based learning in the Aeronautical Information Services (AIS) course, because according to the survey results, among others, the need for AIS visualization in order to improve students' understanding of AIS, while the purpose of this study is to improve the effectiveness, involvement and understanding of students in the AIS course whose material can be more interesting, practical and accessible according to students' needs. This study uses the Research & Development (R & D) research method, and the results of the study are based on the provisions that the AIS course in 1 semester has 16 meetings consisting of 14 theory meetings and 1 meeting for the Mid-Semester Exam (UTS) and 1 meeting for the Final Semester Exam (UAS). This learning video is very important to improve students' understanding which can be accessed anytime, anywhere and repeatedly according to students' needs, both online and offline. ABSTRAKPenelitian ini adalah mendesain pembelajaran berbasis video pada mata kuliah Aeronautical Information Services (AIS), karena menurut hasil survey diantaranya adalah perlunya visualisasi AIS agar dapat meningkatkan pemahaman AIS bagi peserta didik, sedangkan tujuan penelitian ini adalah untuk meningkatkan efektifitas, keterlibatan dan pemahaman peserta didik pada mata kuliah AIS yang materinya dapat menjadi lebih menarik, praktis dan dapat diakses sesuai dengan kebutuhan siswa. Penelitian ini menggunakan metode penelitian Research & Development (R & D), dan hasil penelitian berdasarkan ketentuan bahwa mata kuliah AIS dalam 1 semester ada 16 pertemuan yang terdiri dari 14 pertemuan teori dan 1 pertemuan untuk Ujian Tengah Semester (UTS) dan 1 pertemuan untuk Ujian Akhir Semester (UAS). Video pembelajaran ini sangat penting untuk meningkatkan pemahaman siswa yang dapat diakses kapanpun, dimanapun dan berulang kali sesuai kebutuhan siswa, baik online maupun offline.